Analisis Implementasi Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan di SD Negeri 3 Lemah Mekar - Fikriyah; Fitriyatun Nisa; Lucky Zulkarnaen; Widianingsih (Attractive : Innovative Education Journal, 2024)
An important factor in realizing quality education in schools is school-based management. The purpose of this study is to analyze how the implementation of school-based management improves the quality of education at SDN 3 Lemah Mekar. The research methodology used in this study uses qualitative research with a descriptive approach. The results of the analysis show that school-based management at SDN 3 Lemah Mekar has been implemented well. This can be seen in the work meeting at the beginning of the school year involving all parties at the school. Then, the strategy used in this school uses the PAIKEM strategy (Active, Innovative, Creative, Effective, and Fun Learning), differentiated learning, scientific learning and strategies that lead to 21st century learning. Finally, there is community participation in education for democratic participation. This forum must also ensure openness and responsibility in the education process. It can be concluded that in improving the quality of education, school-based management must involve the participation of the entire school community in implementing principles such as independence, responsibility, participation, and transparency, with the main goal of improving the quality of education that is consistent with all parties involved.